2017
DOI: 10.1590/s1806-92902017000200008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary artemisinin supplementation on productive performance and haematological parameters of broiler chickens

Abstract: -In the present study, we aimed to assess the toxicity of artemisinin on the haematological system and its effect on the productive performance of broiler chickens. Eighteen-day-old chickens were randomly divided into four groups of 30 chickens (three replicates of 10 broilers/group): control group and three experimental groups: ART5 -diet with 5 ppm of artemisinin; ART50 -diet with 50 ppm of artemisinin; and ART500 -diet with 500 ppm of artemisinin. Artemisinin enhanced the productive performances of broiler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…This result confirmed with the histopathological finding ofintestine, which revealed normal intestinal villi; this finding was accepted with findings obtained by Wan et al (2017). In contrast the result obtained by Pop et al (2017) who reported higher body weight and average daily intake of food in broilers fed Artemisia diets than in the control group. The differences could be explained by the different climatic conditions under which feeding experiments (hot and humid seasons) were conducted.…”
Section: Effects Of Diclazuril Thymus Vulgaris and Artemisia Annua On Body Performance In Broilers Chickenssupporting
confidence: 89%
“…This result confirmed with the histopathological finding ofintestine, which revealed normal intestinal villi; this finding was accepted with findings obtained by Wan et al (2017). In contrast the result obtained by Pop et al (2017) who reported higher body weight and average daily intake of food in broilers fed Artemisia diets than in the control group. The differences could be explained by the different climatic conditions under which feeding experiments (hot and humid seasons) were conducted.…”
Section: Effects Of Diclazuril Thymus Vulgaris and Artemisia Annua On Body Performance In Broilers Chickenssupporting
confidence: 89%
“…Table 2 data did not show a significant (p>0.05) difference between the three groups regarding the feed conversion ratio. Pop et al (2017) has shown that Ross 308 broiler chicks reared under normal conditions of temperature and treated with 50 ppm artemisinin showed gains and feed conversion ratio comparable with those of the broiler receiving the conventional diet formulation. The different results of these studies may be accounted by the different chemical composition of the used plant, or by the concentrations, active matter and biological activity of the plant (Amad et al 2011).…”
Section: Resultsmentioning
confidence: 97%
“…12.88%, and 14.70% lower, respectively, compared to the results of our study, while the expected difference among the two hybrids is about 1.71% (according to Management Guide of Cobb 500 Hybrid and Management Guide of Ross 308 Hybrid). Pop et al (2017) noticed that the use of lower concentrations of artemisinin (5 ppm) in Ross 308 broilers (1-28 days) increased the average daily feed intake, the average daily weight gain and improved the feed conversion ratio, while the higher concentration of artemisinin (500 ppm) caused reduced weight gain, inefficient feed conversion, and a lower feed intake. Several researchers have shown that the essential oils act against Gram-negative bacteria, such as Campylobacter jejuni, Escherichia coli, Mycoplasma gallisepticum, Mycoplasma synoviae, Pseudomonas aeruginosa, Salmonella enteridis, or Klebsiella sp.…”
Section: Discussionmentioning
confidence: 99%